Chemistry contribution to stratospheric ozone depletion after the unprecedented water rich Hunga Tonga eruption - Zhang, Jun; Kinnison, Douglas Edward; Zhu, Yunqian; Wang, Xinyue; Tilmes, Simone; Dubé, Kimberlee Robyn; Randel, William J. (Authorea, Inc., 2023)
Following the Hunga Tonga–Hunga Ha’apai (HTHH) eruption in January 2022, stratospheric ozone depletion was observed in the Southern Hemisphere mid-latitudes and Antarctica during the 2022 austral wintertime and springtime. This eruption injected sulfur dioxide and unprecedented amounts of water vapor into the stratosphere. This work examines and quantifies the chemistry contribution of the volcanic materials to the ozone depletion using chemistry-climate model simulations with nudged meteorology. Simulated 2022 ozone and nitrogen oxides (NOx) anomalies show a good agreement with satellite observations. We find that chemistry only contributes up to 6% and 20% ozone destruction at mid-latitudes wintertime and Antarctic springtime respectively. The majority of the ozone depletion is attributed to the internal variability and dynamical changes forced by the eruption. Both the simulation and observations show a significant NOx reduction associated with the HTHH aerosol plume, indicating the enhanced dinitrogen pentoxide hydrolysis on sulfate aerosol.